2020
DOI: 10.7150/ijbs.45231
|View full text |Cite
|
Sign up to set email alerts
|

Function and evolution of RNA N6-methyladenosine modification

Abstract: N6-methyladenosine (m 6 A) is identified as the most prevalent and abundant internal RNA modification, especially within eukaryotic mRNAs, which has attracted much attention in recent years since its importance for regulating gene expression and deciding cell fate. m 6 A modification is installed by RNA methyltransferases METTL3, METTL14 and WTAP (Writers), removed by the demethylases FTO and ALKBH5 (Erasers) and recognized by m 6 A binding proteins, such as YT521-B homology YTH domain-containing proteins (Rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 136 publications
0
63
0
Order By: Relevance
“…METTL3 with catalytic m6A formation function has been proved to play an important role in tumors, brain development, and regulation of stem cell fate [ 33 ]. Current evidence has shown that METTL3 expression is upregulated and mutes SOCS2 through the m6a-dependent pathway to promote LIHC progression [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…METTL3 with catalytic m6A formation function has been proved to play an important role in tumors, brain development, and regulation of stem cell fate [ 33 ]. Current evidence has shown that METTL3 expression is upregulated and mutes SOCS2 through the m6a-dependent pathway to promote LIHC progression [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…As aforementioned, m 6 A modification is a dynamic and reversible epigenetic change ( Zhang et al, 2020 ), which affects the stability and function of RNAs, thereby modulating the pathogenesis and progression of diseases ( Qin et al, 2020 ; Wang et al, 2020 ; Zhu et al, 2020 ). M 6 A modification has been identified in more than 7,000 human genes, and it preferentially occurred at the site of stop codons and long internal exons within the RRACH sequence (R = G or A; H = A, C, or U) ( Dominissini et al, 2012 ).…”
Section: Rna M 6 a Modificationmentioning
confidence: 99%
“…In addition to writers and erasers, “readers” are binding proteins that recognize the chemical signatures important for the regulation of m 6 A modification (Fig. 1 ) [ 27 , 28 ].
Fig.
…”
Section: Regulation Of M 6 a Modificationmentioning
confidence: 99%